MEKANISME BERPIKIR SISTEM DALAM MANAJEMEN PENDIDIKAN ISLAM: SEBUAH KAJIAN INTEGRATIF - Marwazi Marwazi; Kemas Imron Rosadi; Abdi Setiawan; Nispi Syahbani (Hijri, 2026)
Islamic educational institutions face complex challenges in the contemporary era, including globalization, digitalization, and technological disruption. Traditional linear management approaches are inadequate to address this complexity. This study explores systems thinking as a holistic and integrative approach aligned with Islamic philosophy, particularly the concept of tawhid. Using an analytical-descriptive literature review method, this research examines how systems thinking can be applied in planning, organizing, controlling, and utilizing educational systems in Islamic education management. The study integrates Western systems theories (Bertalanffy's General Systems Theory, Senge's Learning Organization, and Kim's Systems Archetypes) with Islamic epistemology. Findings indicate that systems thinking is highly relevant and compatible with Islamic educational philosophy, offering practical frameworks such as Causal Loop Diagrams, Balanced Scorecards, and Management Information Systems. The application of systems thinking can enhance the sustainability and quality of Islamic educational institutions. This research contributes to enriching the literature on Islamic education management by providing an integrative conceptual framework combining systems thinking with Islamic values..